Redesigning curriculum in higher education by using analytical hierarchy process and Spearman Rank Correlation Test - (:unkn) unknown (EuroJournals, Inc., 2011)
In the present study, an application regarding the analysis of stakeholders' claims in the updating process of the undergraduate curriculum of Marmara University Faculty of Technical Education Design and Construction Education Program is discussed. Stakeholders are comprised of related members of the industry and the academicians of related higher education program. The questionnaire carried out within the scope of the study is prepared to determine the claims of stakeholders regarding the practical knowledge and skills which the graduates of the related program used in the vocational applications. The questionnaire forms filled by the stakeholders include their claims and the scaling scores given to each of their claims according to the 5-point Likert scale. The claims of the stakeholders, which are determined by the questionnaires, are ranked using Analytical Hierarchy Process method and Spearman rank correlation test is used in order to examine whether there is a difference between two groups of ranking. Analyzing the ranking of claims, it is found that the stakeholders ask the same claims with a different ranking. According to the results of Spearman rank correlation test, it is determined that there is no statistically significant difference between the ranking of claims of the stakeholders with 5% confidence interval. At the end of the study, the suggestions regarding how the obtained results could be benefitted from in the re-design process of the undergraduate curriculum of the higher education program are discussed. © EuroJournals Publishing, Inc. 2011.
Keywords: Analytical hierarchy process; Quality in higher education; Redesign of the undergraduate curriculum; Spearman rank correlation test